Function and Zoning Mapping in Urban Tourism Facilities (Case Study: Scientia Square Park and Tebet Eco Park) - Angelina, Angelina; Ratnasari, Anisza (Lakar: Jurnal Arsitektur, 2025)
The density of urban areas caused by urban development and urbanization flows causes various problems that have an impact on the activities and routines of urban communities. Limited activities and space for movement are one source of boredom and stress for city residents. In dense urban areas, the existence of green open spaces is very limited so there is a lack of space for physical activities such as sports and recreational activities to reduce feelings of boredom and stress. Urban tourism is one of the urban tourism resources, which functions as a temporary diversion, pause and a short stop for urban communities from the hustle and bustle of the city. Scientia Square Park and Tebet Eco Park are examples of green spaces in densely populated areas that are suspected of being able to divert urban communities from the density of city activities. Under human needs where they need entertainment and relaxation areas to relax the mind, the study results show that these two parks provide space for the surrounding community to interact socially, relax, and become a place of recreation. This study, which is qualitative research, aims to map the functions and zones of open space activities through physical observation. Data search was carried out using the place-centered mapping technique. Photos are visualized graphically and analyzed interpretively based on the zones and functions of the activities. The hope for the future is that by knowing the function and zoning of activities, urban tourism can be presented through open spaces that can support the restoration function of dense urban activities.